DESKRIPSI PEMAHAMAN SISWA SMA TENTANG GRAFIK USAHA DAN ENERGI - Purba, Debora Tresia; Werdhiana, I Komang (Universitas Tadulako, 2021)
This study aimed to describe students’ understanding on graph representation while solving Work and Energy problems. This study used descriptive qualitative method. 30 students were given a test before selecting 6 respondents for further investigation. These 6 respondents consisted of 2 of high ability category, 2 of medium category, while the other 2 were in low category. The data in this study were collected through observation, written tests in the form of descriptions and interviews. Data were analysed using the stages of data reduction, presentation, and conclusion. Based on the results of the study, it was found that the ability of high school students to explain the graph of work and energy was in low category. This is due to several factors, including a lack of interest in working on graph problems that require interpretation, graph questions that have never been tested by the teacher, making it difficult for respondents to work on these questions. Also, students found it difficult to understand questions about the slope of the graph. Based on the results of tests and interviews, it was shown that students had difficulty interpreting the area under the graph, misinterpreting and misunderstood the graph. In addition, students could not read graphs and only answer tests by making up the answers, and did not understand the topic of work and energy.